The Effect of Blockholder Ownership and Audit Committee on Financial Performance of Property & Real Estate Companies Listed on The Indonesia Stock Exchange For The 2020–2024 Period - Andini Hardiansyah Putri; Siti Sundari (LP2M IAIN Palopo, 2026)
This study aims to examine the effect of blockholder ownership and audit committee on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Financial performance is measured using Return on Assets (ROA). The study is motivated by inconsistent findings in previous studies regarding the effectiveness of corporate governance mechanisms in improving company profitability. This research employed a quantitative approach using multiple linear regression analysis. The population consisted of property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using purposive sampling, resulting in 41 companies with a total of 205 observation data. Data were collected through documentation techniques using annual reports and financial statements published by the companies. Blockholder ownership was measured based on the percentage of share ownership held by shareholders owning at least 5% of total outstanding shares, while the audit committee variable was measured by the number of audit committee members. The results indicate that blockholder ownership does not have a significant effect on financial performance. In contrast, the audit committee has a negative and significant effect on financial performance. Simultaneously, blockholder ownership and audit committee significantly affect financial performance. These findings suggest that the existence of corporate governance mechanisms in a formal structure does not necessarily improve company profitability without effective supervisory implementation. This study provides implications for companies, investors, and policymakers regarding the importance of improving the effectiveness of corporate governance practices rather than merely fulfilling formal governance structures. The findings also suggest that companies should focus on enhancing the competency and supervisory quality of audit committee members to optimize financial performance. Future studies are recommended to include additional governance variables, broader industrial sectors, and alternative financial performance measurements to obtain more comprehensive results.